FAR-RED INSENSITIVE 219/JAR1 Contributes to Shade Avoidance Responses of Arabidopsis Seedlings by Modulating Key Shade Signaling Components - Swain, Swadhin; Jiang, Han-Wei; Hsieh, Hsu-Liang (Frontiers in Plant Science, 2017)
To receive an ample amount of light, Plants use elongation growth in response to vegetation shade. The combined interaction of light and hormones, including jasmonic acid (JA) signaling controls this elongation. However, the detailed molecular mechanisms underlying the response are still emerging. FAR-RED INSENSITIVE 219/JASMONATE RESISTANCE 1 (FIN219/JAR1), a cytoplasmic localized JA-conjugating enzyme, integrates far-red light and JA signaling. Here, we report that FIN219/JAR1 negatively regulates shade-induced hypocotyl elongation and gene expression in Arabidopsis seedlings in response to shade. In turn, simulated shade reduces FIN219 protein accumulation. Analysis of phyA 211 fin219-2 double mutants indicated that FIN219 and phyA are synergistic in regulating shade-induced hypocotyl elongation and gene expression. Moreover, FIN219 differentially affected the expression of the shade-signaling bHLH factors PIF5 and PAR1, thereby increasing the expression of the auxin-response genes IAA29 and SAUR68 on exposure to shade. Furthermore, the protein level of CONSTITUTIVE PHOTOMORPHOGENIC1 (COP1) was affected in both fin219 mutants and overexpression lines as compared with the wild type under shade. Intriguingly, ectopic expression of FIN219 inhibited the nuclear accumulation of COP1 in response to shade. Further co-immunoprecipitation studies revealed that FIN219 interacted with COP1 and phyA under shade. Therefore, FIN219/JAR1 may play a vital role in modulating the Arabidopsis response to simulated shade via multiple layers of molecular mechanisms.